2012
DOI: 10.1002/ctpp.201200045
|View full text |Cite
|
Sign up to set email alerts
|

Phase Diagram of Bilayer Electron‐Hole Plasmas

Abstract: We investigate exciton bound-state formation and crystallization effects in two-dimensional electron-hole bilayers. Performing unbiased path integral Monte Carlo simulations all quantum and Coulomb correlation effects are treated on first principles. We analyze diverse pair distribution functions in dependence on the layer separation, particle density and hole-to-electron mass ratio and derive a schematic phase diagram for the neutral mass-asymmetric bilayer system. Our simulations reveal a great variety of po… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
29
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 37 publications
(126 reference statements)
3
29
0
Order By: Relevance
“…The paper by Schleede et al [6] considers theoretically the example of electron-hole bilayers that add quantum correlation effects to the Coulomb coupling. The paper by Schleede et al [6] considers theoretically the example of electron-hole bilayers that add quantum correlation effects to the Coulomb coupling.…”
Section: Strong Coupling Effects In Complex Plasmasmentioning
confidence: 99%
“…The paper by Schleede et al [6] considers theoretically the example of electron-hole bilayers that add quantum correlation effects to the Coulomb coupling. The paper by Schleede et al [6] considers theoretically the example of electron-hole bilayers that add quantum correlation effects to the Coulomb coupling.…”
Section: Strong Coupling Effects In Complex Plasmasmentioning
confidence: 99%
“…The gas–liquid transition, features of the liquid exciton phase, and transition into the superfluid phase were studied as a function of the interlayer spacing ℓ in Lozovik and Berman . The Wigner crystallization and instability of the liquid in the electron–hole coupled systems were treated within the RPA and Monte Carlo numerical simulations in Swierkowski et al The phase diagram and the ordered structures in a bilayer electron–hole plasma were investigated using the path‐integral Monte Carlo approach in Schleede et al…”
Section: Introductionmentioning
confidence: 99%
“…The gas-liquid transition, features of the liquid exciton phase, and transition into the superfluid phase were studied as a function of the interlayer spacing in Lozovik and Berman. [3] The Wigner crystallization and instability of the liquid in the electron-hole coupled systems were treated within the RPA and Monte Carlo numerical simulations in Swierkowski et al [4,5] The phase diagram and the ordered structures in a bilayer electron-hole plasma were investigated using the path-integral Monte Carlo approach in Schleede et al [6,7] As shown by Keldysh, the multi-valley band structure facilitates the formation of the electron-hole liquid (EHL). According to Andrushin et al, [8] the multi-flavour EHP inherent in the bulk many-valley semiconductors has the unconventional Coulomb screening.…”
Section: Introductionmentioning
confidence: 99%
“…Experimentally, multifaceted attempts have been made to observe the condensed state of excitons, e.g., in photoexcited semiconductors [5][6][7][8][9], unconventional semiconductor/graphene systems [10][11][12][13][14], electrostatic traps [15], or neutral electron-ion quantum plasmas [16]. Theoretically, a possible crossover between a Bardeen-Cooper-Schrieffer (BCS) electron-hole pair condensate and a Bose-Einstein condensate (BEC) of preformed excitons has been of topical interest [4,[17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%